A case of adult Still's disease with macrophage activation syndrome complicating acute pancreatitis. Issue 1 (2nd January 2017) - Kurushima, Shota; Horai, Yoshiro; Nagata, Koh; Nakashiki, Suguru; Iwamoto, Naoki; Ichinose, Kunihiro; Nakamura, Hideki; Kawakami, Atsushi
Abstract: A man in his twenties was admitted to our hospital for evaluation of pyrexia and a skin rash. He was diagnosed with adult Still's disease and an extremely high serum ferritin concentration. His laboratory findings were compatible with macrophage activation syndrome. He subsequently developed abdominal pain, which was diagnosed as acute pancreatitis by contrast-enhanced computed tomography. Acute pancreatitis should be noted as a possible severe complication of adult Still's disease in patients with a very high serum ferritin concentration and macrophage activation syndrome.